1976
DOI: 10.1002/1097-0142(197608)38:2<915::aid-cncr2820380239>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse cystic glandular malformation of the stomach associated with adenocarcinoma.Case report and review of the literature

Abstract: A 60-year-old man was found to have diffuse cystic glandular malformation and adenocarcinoma of the stomach. Review of the literature revealed one similar reported case and five others with diffuse heterotopic cystic malformation only. Clinically, the lesion is associated with gastrointestinal symptoms, and radiologically , it can mimic diffuse gastric carcinoma, lymphoma, or polyposis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 6 publications
2
16
1
Order By: Relevance
“…The diffuse heterotopic submucosal cystic malformations (submucosal cysts) of the stomach have been reported under several names, including multiple diffuse cystic disease [1], diffuse submucosal cystic disease [2], diffuse cystic glandular malformation [3], heterotopic gastric glands [6], and heterotopic submucosal gastric cysts [7]. These cysts have been found in stomachs resected for gastric carcinoma, and their possible association with gastric carcinoma has been suggested [1][2][3].…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…The diffuse heterotopic submucosal cystic malformations (submucosal cysts) of the stomach have been reported under several names, including multiple diffuse cystic disease [1], diffuse submucosal cystic disease [2], diffuse cystic glandular malformation [3], heterotopic gastric glands [6], and heterotopic submucosal gastric cysts [7]. These cysts have been found in stomachs resected for gastric carcinoma, and their possible association with gastric carcinoma has been suggested [1][2][3].…”
Section: Discussionsupporting
confidence: 52%
“…An association of submucosal cysts of the stomach with gastric carcinoma has been suggested by others [1][2][3]. Iwanaga et al suggested that submucosal cysts may not be precancerous lesions, but be paracancerous [2].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations